KONSEP HALĀLAN ȚAYYIBAN DALAM PERSPEKTIF ISLAM - Umar, As’ad (Irtifaq, 2014)
Halāl means things that should and can be done because it is free or not bound by the provisions of the ban. Or anything that is free from worldly dangers and hereafter. Halāl food is said to be at least must meet three criteria, namely the substance halal, the manner of obtaining and the manner of processing. Țayyib food means 'healthy food, proportionate and safe'. Healthy means having sufficient and balanced nutrition. Proportional means in accordance with the needs of eaters, not excessive and not reduced. While safe means not cause disease, in other words, according to human safety and ukhrawi. This study includes qualitative research. Therefore, the data collected through the reading and study of the text (text reading) as well as interviews with people who are competent in the field of the problems that the authors studied, and then the results were analyzed using descriptive analytical techniques. The results of this study concluded that food halālan ţayyiban is all halal food for consumption, good for the soul and not harm the human body and mind, it contains substances that are needed by the human body and consumed in doses sufficient and balanced. Keywords: Halālan, Țayyiban